Sustainable Marine Aquaponics: Effects of Shrimp to Plant Ratios and C/N Ratios - Chu, Yu-Ting; Brown, Paul B. (Frontiers in Marine Science, 2021)
Integrated aquaponic food production systems are capable of producing more food on less land using less water than conventional food systems, and marine systems offer the potential of conserving freshwater resources. However, there have been few evaluations of species combinations or operational parameters in marine aquaponics. The goal of this experiment was evaluation of stocking density ratio of Pacific whiteleg shrimp (Litopenaeus vannamei) to three edible halophytes (Atriplex hortensis, Salsola komarovii, and Plantago coronopus) with two C/N ratios in a 3 × 2 factorial design. There were three stocking density ratios (shrimp: plant), 2:1, 3:1, and 5:1; and two C/N ratios, 12 and 15. The results indicated that stocking density ratio exerted a significant impact on shrimp growth. Shrimp reared in 2:1 and 3:1 treatments had better growth performance. In contrast, plants were affected by both stocking density ratio and C/N ratio. Halophytes grown in stocking density ratios of 3:1 and 5:1 with a C/N ratio of 15 had better growth performance and nutrient content. The concentrations of TAN and NO2– were below 0.2 mg/L throughout the experiment, including the higher stocking density ratio treatments. In conclusion, the stocking density ratio of 3:1 with a C/N ratio of 15 was suggested as the optimal condition for the operation of marine aquaponics in which whiteleg shrimp and the three halophytes are target crops.